Produção e caracterização de queijos tipo pecorino à base de leite de vaca enriquecidos com ingredientes funcionais - Mews, Laura Alice Levien (2015)
The search for health-promoting foods challenges the food industry. Therefore many studies are required in order to investigate the development of new products that retain the same nutritional characteristics. The use of functional ingredients has been an useful alternative for the nutritional and functional enrichment of new products. In this context, the aim of this study was to develop and characterize the physical-chemical composition of a cheese enriched with a guava pulp microencapsulated and inulin and then evaluating their behavior during the respective storage period of 20 days under 5°C. The first stage proceeded by drying the guava pulp with a spray dryer to obtain a 5μm average particle size microencapsulated with 45.46% of efficiency and a 85.00% of microencapsulation efficiency. The guava pulp microencapsulated (MG) was previously characterized by Scanning electron microscope, Reflection Absorption Infrared Spectroscopy, Ultraviolet-visible spectroscopy, X-ray diffraction and thermo-gravimetry, which provided the evaluation of its functional and nutritional quality. The MG was considered a functional ingredient rich in lycopene (natural antioxidant) as provided by the total content of carotenoids higher (64.88 ± 0.52 μg.g-1) than the guava pulp (32.62 ± 4,17 μg.g-1). Its stability at room temperature, compared to the reaction in presence and absence of light was studied, and in the end of 45 days the MG in presence of light decreased its total of carotenoids by 96.00%. In a second step it was proceeded the preparation of cheese formulations enriched with MG and inulin, defined by 22 Central Composite Rotational Delineation totalizing 12 samples. The instrumental texture profile, shear analysis, color, water activity (aw), carotenoids, antioxidant activity (DPPH and ABTS), moisture, lipids, proteins, carbohydrates (obtained by difference), ashes, sodium chloride, dry matter (DM), fat in dry matter (FDM), pH and caloric value were evaluated at the end of 20 days of maturation under refrigeration. Thus, each response variable showed a quadratic model, which was predictive in descending order of the correlation coefficient for lipids, carotenoids, chromaa*, GES, hºab and caloric value (R2 (%) = 96.55 ; 93.12; 88.31; 80.39; 80.29; 78.50, respectively). The T4 formulation stood out in the study with the greatest enrichment with carotenoids (5.0 μg.g-1) and inulin, which fulfills its role as a fat substitute. T4 stood out in all generated models, a fact also confirmed by the principal component analysis.